A PERCEPÇÃO DOS IDOSOS A PARTIR DAS ENTREVISTAS CAMINHADAS - Costa, Tanara Gomes da; Medvedovski, Nirce Saffer; Sopeña, Sirlene de Mello; Cardoso, Anelize Milano; Portella, Adriana Araújo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work integrates research in development, with international partnership, led by researchers from the United Kingdom and Brazil. This research has as main objective to investigate how the sense of place is experienced by the elderly of different social contexts that reside in different districts in Brazil and the United Kingdom. Through the application of methods of data collection, it seeks to identify how the elderly feel in their own neighborhood, facing all the adversities that exist on a daily basis, pointing out negative and positive points of living in that place. As a research tool, a visual method conducted by elderly participants is used to encourage spontaneous reports of experiences of the place where they live. For that, walking with elderly people was carried out in three neighborhoods, in different contexts, in the city of Pelotas. In the analysis of the data collection of these walks with the elderly, categories were extracted from the reports that had consent of recording of the participants. From this analysis, positive and negative points were identified in the three neighborhoods, which aims to contribute to public policies with actions and activities developed directly or indirectly, with the participation of the elderly.